The causal relationship between emotion regulation and suicidal ideation mediated by marital satisfaction in earthquake-stricken women - Behrouz , Behzad; Golmohammadian , Mohsen; Hojatkhah , Seyedmohsen (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was aimed to determine the causal relationship between emotion regulation and suicidal ideation mediated by marital satisfaction in earthquake-stricken women. Method: The research method was descriptive and correlational, and the statistical population included 21988 married women with earthquake experience in Sarpol Zahab city in 2018. In this study, 600 women were selected by simple random sampling method, and they completed the Cognitive Emotional Regulation Questionnaire (Grenfsky et al., 2001), Suicidal Ideation (Beck, 1979), and Short Form Marital Satisfaction (Enrich, 1979). Data analysis was conducted using Pearson correlation coefficients and multivariate regression and structural equation modeling with SPSS-24 and AMOS-22 software. Results: The results showed that the conceptual model of the research had an acceptable fit. In general, in the proposed research model, the results showed that emotion regulation has a relationship both directly and indirectly with suicidal ideation through marital satisfaction in earthquake-stricken women. Also, the results showed that there is a positive and significant relationship between maladaptive emotional strategy and suicide ideation. Also, there is a negative and significant relationship between maladaptive emotional strategy and marital satisfaction (P